Eight darmarane-type saponins isolated from the roots of Panax notoginseng - Kaunda Joseph Sakah; Tao Wang; Lili Liu; Yue Chen; Lifeng Han; Yi Zhang (Elsevier, 2013)
Eight darmarane-type saponins, named as sanchirhinoside D (1), 3β,6α-20(S)-6,20-bis(β-d-glucopyranosyloxy)-3-hydroxy dammar-24-en-12-one (2), 20(R)-ginsenoside Rg3 (3), ginsenosides F2 (4) and Rd (5), gypenoside XVII (6), ginsenosides Rb1 (7) and ginsenoside V (8) were isolated from the 70% ethanol extract of Panax notoginseng roots by silica gel, octadecyl silane (ODS) column chromatography and HPLC, and identified by chemical and physical methods, especially by spectral analysis. Among them, 1 was a new compound and 2 was a new natural product.